2014
DOI: 10.3390/molecules191117578
|View full text |Cite
|
Sign up to set email alerts
|

The Sustained Delivery of Resveratrol or a Defined Grape Powder Inhibits New Blood Vessel Formation in a Mouse Model of Choroidal Neovascularization

Abstract: The objective of this study was to determine whether resveratrol or a defined, reconstituted grape powder can attenuate the formation of new blood vessels in a mouse model of choroidal neovascularization (CNV). To accomplish this objective, C57BL/6J mice were randomized into control or treatment groups which received either resveratrol or grape powder by daily oral gavage, resveratrol or grape powder delivered ad libitum through the drinking water, or resveratrol by slow release via implanted osmotic pumps. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…The effect of oral resveratrol (25–50 mg/kg/day) has been shown to reduce macrophage infiltration and inflammatory and angiogenic (VEGF) cytokines in the RPE-choroid complex in a murine model of laser CNV [ 44 ]. Kanavi et al [ 45 ] found that resveratrol inhibited Akt/protein kinase B activity in choroidal endothelial cells, which is consistent with the anti-migratory properties of resveratrol that have been observed in vitro . Resveratrol also inhibits branching and network formation of choroidal endothelial cells, in vitro correlates of angiogenesis.…”
Section: Discussionsupporting
confidence: 62%
“…The effect of oral resveratrol (25–50 mg/kg/day) has been shown to reduce macrophage infiltration and inflammatory and angiogenic (VEGF) cytokines in the RPE-choroid complex in a murine model of laser CNV [ 44 ]. Kanavi et al [ 45 ] found that resveratrol inhibited Akt/protein kinase B activity in choroidal endothelial cells, which is consistent with the anti-migratory properties of resveratrol that have been observed in vitro . Resveratrol also inhibits branching and network formation of choroidal endothelial cells, in vitro correlates of angiogenesis.…”
Section: Discussionsupporting
confidence: 62%
“…Kanavi and colleagues have shown that sustained delivery of resveratrol or a defined grape powder inhibited new blood vessel formation in a mouse model of CNV. 35 The authors argued that the antiangiogenic effects of these compounds are comparable to those obtained with ranibizumab or bevacizumab, which are recombinant monoclonal antibodies used to blocks angiogenesis in human patients. 35 …”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 99%
“…Kanavi et al have shown that sustained delivery of resveratrol or a defined grape powder inhibited new blood vessel formation in a mouse model of CNV. 35 The authors argued that the antiangiogenic effects of these compounds are comparable to those obtained with ranibizumab or bevacizumab, which are recombinant monoclonal antibodies used to blocks angiogenesis in human patients. 35 Metabolic syndrome is a disorder of energy use and storage and is clinically diagnosed when three of the five following conditions are present: abdominal obesity, higher blood pressure, elevated fasting plasma glucose, excessive serum triglycerides, and decrease in high-density cholesterol (HDL) levels.…”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 99%
“…Recent reports have shown that RSV can suppress hypoxia-induced VEGF expression and secretion in an immortalized endothelial cell line derived from monkey retina/choroid [7], human adult RPE cells [8] and macrophages [9]. Furthermore, systemic application of RSV inhibits angiogenesis in murine CNV models [9, 10]. In this study, we show for the first time, that the inhibition of VEGF/VEGFR2 signaling in low passage human RPE and endothelial cells is mediated, at least in part, through SIRT1, providing evidence for using RSV or targeting SIRT1 as a potential therapeutic approach for CNV.…”
Section: Introductionmentioning
confidence: 99%